Us and them. The role of persuasive and manipulative strategies in creation of public enemies = My i oni. Rola struktur osobistych i manipulacyjnych w tworzeniu wrogów publicznych - Petrovićová, Katarina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Cicero was during his live one of the most successful orators in Rome. His ability to express his meanings and ideas in the most persuasive way did not impress only his contemporaries, but influenced the art of rhetoric generally. We admire the argumentative strength, the verbal copiousness, the most striking rhe?torical skill is, however, his manipulative force, the allocution of the listener, "ut moveatur vehementius" (Cic.Brut.49, 185).
Keywords: rhetoric; political discourse; persuasion; manipulation; labelling; public enemy; Cicero, Marcus Tullius (106-43 a.C.); Zeman, Miloš (polityk czeski; 1944- ); retoryka; dyskurs polityczny; perswazja; manipulacja; wróg publiczny